Uso da fitossociologia na avaliação da efetividade da restauração florestal em uma várzea degradada do rio Mogi Cuaçu, SP - Da Nóbrega, Assíria Maria Ferreira; Vaieri, Sérgio Valiengo [UNESP]; De Paula, Rinaldo César [UNESP]; Da Silva, Sérgio Adriano; Rêgo, Norton Hayd (My University, 2007)
This study objective was to evaluate the effective revegetation in a Mogi Guaçu River degraded floodplain area, located at Luiz Antonio municipality (21° 31' S e 47° 55' W), São Paulo State, Brazil. Two native riparian forest remnants (RIP1 and RIP2) and three 10-year-old reforested areas, planted of native species (R1, R2 and R3), were analyzed by using phytosociological describers of the arboreal stratum (trees with DBH ≥ 5 cm) as indicators. The arboreal stratum inventory was accomplished by 180 plots (10 × 10 m each), 60 representing every native forest and 20 for every reforested area. A total of 60 arboreal species was recorded, only six species (Cecropia hololeuca, Crotón urucurana, Genipa americana, Inga striata, Nectandra megapotamica e Peltophorum dubium) occurring in all the five studied areas. Seventeen species were common to both native forests, and nine species were recorded in all the reforested areas. Sebastlania commersonlana and Guarea macrophyllawere recorded in the native forests (RlP1 and RIP2), and Cecropia hololeuca, Croton urucurana and Inga striata occurring in all the reforested areas, were the species that best characterize the physiognomy of local diversity and were the most important among the studied species. The results showed that the rehabilitation of the areas made by the reforestation created conditions to implant forests with similar structures of the adjacent natural remainders. The reforestation with native species performed in the degraded floodplain of Mogi Guaçu River, initially with the predomination of invasive grasses, has been effective at the first stage of the ecological restoration process. The reforestation is making possible the natural regeneration of species from the adjacent remnants, what indicates that the similarity between planted forests and the native ones are rising through the time. The phytosociology, accomplished ten years after the planting date, is adequate to evaluate the effectiveness of the reforestation during the restoration process of degradated areas in the Mogi Guaçu floodplain.
The use of phytosociology in effective evaluation of forest restoration in a Mogi Guaçu River degraded floodplain, São Paulo, Brazil
Keywords: Diversity index; Floristic similarity; Reforestation; Riparian forest; Effective revegetation; Floodplain; Forest restoration; Biodiversity; Ecology; Flood control; Rivers; Floods; Phytosociology